Association between mitochondria-related genes and cognitive performance in the PsyCourse Study - Oraki Kohshour, Mojtaba; Schulte, Eva C.; Heilbronner, Urs; Budde, Monika; Kalman, Janos L.; Senner, Fanny; Heilbronner, Maria; Reich-Erkelenz, Daniela; Schaupp, Sabrina K.; Vogl, Thomas; Adorjan, Kristina; Anghelescu, Ion-George; et al. (Journal of affective disorders, 2023)
Background - Mitochondria generate energy through oxidative phosphorylation (OXPHOS). The function of key OXPHOS proteins can be altered by variation in mitochondria-related genes, which may increase the risk of mental illness. We investigated the association of mitochondria-related genes and their genetic risk burden with cognitive performance. - Methods - We leveraged cross-sectional data from 1320 individuals with a severe psychiatric disorder and 466 neurotypical individuals from the PsyCourse Study. The cognitive tests analyzed were the Trail-Making Test, Verbal Digit Span Test, Digit-Symbol Test, and Multiple Choice Vocabulary Intelligence Test. Association analyses between the cognitive tests, and single-nucleotide polymorphisms (SNPs) mapped to mitochondria-related genes, and their polygenic risk score (PRS) for schizophrenia (SCZ) were performed with PLINK 1.9 and R program. - Results - We found a significant association (FDR-adjusted p < 0.05) in the Cytochrome C Oxidase Assembly Factor 8 (COA8) gene locus of the OXPHOS pathway with the Verbal Digit Span (forward) test. Mitochondrial PRS was not significantly associated with any of the cognitive tests. - Limitations - Moderate statistical power due to relatively small sample size. - Conclusions - COA8 encodes a poorly characterized mitochondrial protein involved in apoptosis. Here, this gene was associated with the Verbal Digit Span (forward) test, which evaluates short-term memory. Our results warrant replication and may lead to better understanding of cognitive impairment in mental disorders.
Online verfügbar 6 Januar 2023, Artikelversion 9 Januar 2023
Gesehen am 23.03.2023